Successful treatment of diffuse lipoid pneumonitis with whole lung lavage. - Chang, H. Y. (1993)
Diffuse lipoid pneumonitis is rare. Prednisolone can be beneficial, but no other method of treatment has been tried. The first case of diffuse lipoid pneumonitis successfully managed with whole lung lavage is described.